Sierra Leone : PIM in a Donor-Dependent Post-Conflict Economy - Foday, Yusuf; Addison, Douglas; Petrie, Murray (World Bank, Washington, DC, 2014)
Sierra Leone is a small, fragile, post-conflict state on the coast of West Africa. As a consequence, Sierra Leone was one of the largest beneficiaries of foreign aid as a share of gross domestic product (GDP) and aid per capita. Projects focusing on reconstruction of basic infrastructure and on capacity-building for reestablishment of core government functions featured prominently in the government's development budget. The post-conflict infrastructure gap was quite large. As peace was consolidated, the level of external assistance has gradually declined from 15.5 percent of GDP in 2002 to 5.2 percent of GDP in 2008 as donors phased out their post-conflict allocations and the nation s GDP expanded rapidly. Looking ahead, the government seeks to restore a high rate of real growth and poverty reduction through increased public and private investment. The government does not operate a capital investment budget; rather it maintains a development budget that seeks to record most externally financed projects, government contributions to those projects, and expenditures on the government's own projects. This case study is based on work done for the 2009-10 public expenditure review.